THE RESOURCE POTENTIAL OF ART THERAPY IN THE SYSTEM OF PSYCHOLOGICAL SUPPORT FOR MEDICAL STAFF (Psychology Travelogs, 2025)
The article highlights the current issue of psychological support for medical staff in conditions of significant professional challenges and intense workloads. Medical workers are constantly faced with a high level of stress, excessive responsibility and emotional tension, which leads to an increased risk of developing burnout syndrome, emotional exhaustion and psychosomatic disorders. In this context, the search for effective tools to support their psychological well-being becomes of particular importance, among which art therapy occupies an important place. The paper examines theoretical and practical approaches to the use of art therapeutic methods in the system of psychological assistance to medical professionals. It is emphasized that art therapy is a multidimensional method that combines the possibilities of creative self-realization, emotional regulation and development of internal resources of the individual. Art therapy techniques allow medical workers to restore internal balance, reduce anxiety and tension, improve communication skills and gain new experience in overcoming stressful situations. The purpose of the study is to determine and substantiate the resource potential of art therapy in the system of psychological support for medical personnel, as well as analyze its effectiveness in maintaining professional health. Special attention is paid to the study of how art therapy practices contribute to the formation of self-regulation skills, the development of positive coping strategies and increasing the level of psychological resilience of specialists. The conclusions emphasize that the systematic use of art therapy in working with medical workers contributes to the preservation of their psycho-emotional well-being, activation of creative potential, development of emotional stability and formation of the ability to harmoniously interact with the professional environment. At the same time, the integration of art therapy methods into the psychological support system in healthcare institutions is considered a promising direction, which ensures not only an increase in the quality of life of medical workers, but also the overall effectiveness of the provision of medical services.
Keywords: art therapy; medical personnel; professional activity; psychological support; resources; resilience; self-regulation; stress resistance; creative potential